Solidarity between Generations in Extended Families: Old-Age Income as a Way Out of Child Poverty?. (12th October 2019) - Verbist, Gerlinde; Diris, Ron; Vandenbroucke, Frank
Abstract: We analyse intergenerational solidarity within multigenerational households (MGHs) and assess how the formation of these households is related to poverty across European countries. Our aim is to assess how this type of household is a coping strategy with respect to financial distress for families with children. Using data from EU Statistics on Income and Living Conditions (EU-SILC), we examine three specific empirical questions with regards to this complex form of intergenerational solidarity, notably (i) we identify to what extent co-residence within MGHs is financially beneficial to the young and/or the old generation; (ii) we analyse how the income brought into these households by the old generation impacts on child poverty, and (iii) we test how sensitive this impact is to hypotheses about the way resources are shared in the household. We define MGHs as those households where three generations cohabit. The results indicate that the formation of MGH operates mainly as solidarity from older to younger generations. Although not designed for this purpose, pensions alleviate child poverty in countries where MGH is most prevalent.